2019
DOI: 10.2196/13477
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Engagement With an Online Health Community and Changes in Patient Activation and Health Care Utilization: Longitudinal Web-Based Survey

Abstract: Background Participation in online health communities (OHCs) is a popular trend in the United Kingdom. However, so far, no evidence exists to indicate an association between participation in OHCs and improved health outcomes. Objective This study aimed to (1) determine changes in patient activation over 3 months in new users of an OHC, (2) describe patterns of engagement with an OHC, (3) examine whether patients’ characteristics at baseline were associa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…Online patient communities may even impact health care costs. A longitudinal study of new enrollees of HealthUnlocked, a collection of online patient communities in the United Kingdom, revealed declines in emergency room visits [36]. Much more research is needed to fully understand the range of benefits people experience in these communities and how to amplify beneficial experiences.…”
Section: What Are Ways Social Media Can Be Used To Improve Physical and Mental Well-being?mentioning
confidence: 99%
“…Online patient communities may even impact health care costs. A longitudinal study of new enrollees of HealthUnlocked, a collection of online patient communities in the United Kingdom, revealed declines in emergency room visits [36]. Much more research is needed to fully understand the range of benefits people experience in these communities and how to amplify beneficial experiences.…”
Section: What Are Ways Social Media Can Be Used To Improve Physical and Mental Well-being?mentioning
confidence: 99%
“…There is growing evidence that supports patient activation to guide interventions and assist in implementing strategies to activate individuals for self-management [ 4 , 5 ]. Previous studies have linked patient activation with positive health outcomes, such as decreased health care utilization [ 6 , 7 ], reducing symptoms [ 8 , 9 ], and improving quality of life [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, a recent study indicated that patients gained empowerment through OHCs, which was positively related to patient commitment to the physician and to patient compliance with the proposed treatment [ 2 ]. Moreover, there is evidence that users who are high engagers (such as superusers who are themselves patients) exhibit the greatest improvement in patient activation measure (PAM; a measure that captures the extent to which people feel engaged and confident in taking care of their condition) in HealthUnlocked OHCs, even if the average change in PAM across all levels of engagement is not clinically meaningful [ 39 ].…”
Section: Discussionmentioning
confidence: 99%